Hands-On Design Patterns with Kotlin: Build Scalable Applications Using Traditional, Reactive, and Concurrent Design Patterns in Kotlin - Soshin, Alexey (Packt Publishing, Limited, 2018)
Design patterns enable you to speed up the development process by providing tested, proven development paradigms. Reusing design patterns helps prevent complex issues, improves your code base, promotes code reuse, and makes the architecture more robust. This book will ease the adoption of design patterns in Kotlin and provide best practices.